The effect of different precursor solutions on the structural, morphological, and optical properties of nickel oxide as an efficient hole transport layer for perovskite solar cells - Muniandy, Subathra; Idris, Muhammad Idzdihar; Mohammed Napiah, Zul Atfyi Fauzan; Norddin, Nur Bahirah; Rashid, Marzaini; Mahmood Zuhdi, Ahmad Wafi; Bradley, Luke (University Putra Malaysia Press, 2023)
Perovskite solar cell (PSC) technologies have recently become a popular research topic. The hole transport layers (HTL) are important in establishing stable and efficient PSC by regulating charge absorption, interlayer recombination losses, and band alignment. Spiro-OMeTAD was extensively used as the HTL to fabricate highly efficient PSCs. Despite Spiro-OMeTAD having the benefit of providing high PCEs, it is costly, hazardous to the ecology, and cannot provide high efficiencies in the lack of additional additives that can reduce their stabilities. Inorganic HTL, specifically nickel oxide (NiO), has garnered much interest due to its low-cost, enhanced mobility, and strong stability to attain high efficiency. This study investigated different precursor solutions of NiO synthesis (Method I, II, and III) and deposited using the spin coating approach. The films were annealed at different annealing temperatures (400°C, 550°C, and 700°C) and evaluated by X-ray powder diffraction (XRD), UV-Vis spectroscopy, and Scanning electron microscopy (SEM) to test their structural, morphological, and optical characteristics, respectively. The findings of XRD revealed that a higher annealing temperature increases the crystallite size and decreases the microstrain through the study from Scherrer’s and Williamson-Hall’s (WH) equations. From the SEM analysis, the films show uniformity, large crystals, and agglomeration of particles. The annealing temperature from 400°C to 700°C reduced bandgap energy from 3.6 eV to 2.1 eV. According to the result, NiO produced at an annealing temperature of 700°C (Method I) exhibited the best characteristics and might be a viable option for HTL in PSCs.